Manajemen Pengembangan Kurikulum Berbasis Madrasah di MTs Ma’arif NU Kota Malang - Nursabila, Eka; Nuraini, Indah Ayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Curriculum development has a very crucial role in the education process, especially in the learning process. The achievement of learning depends on the management of curriculum development that carried out in each school. This study aims to determine the management of madrasa-based curriculum development that carried out at MTs Ma'arif NU Malang City. This research used descriptive qualitative method through interviews, observation, and documentation. The subjects studied were curriculum documents that had been developed, the subjects interviewed were the head of the madrasa, vice of curriculum, and teacher representatives. The results showed that the management of curriculum development at MTs Ma'arif NU Malang City includes planning, implementation, and evaluation. The implementation of the curriculum is carried out in macro and micro. Macro implementation by the curriculum development team, by the head of the madrasa and the vice of the curriculum to design selective programs such as aswaja deed and tahfidz programs. While the implementation of the micro curriculum is carried out by each subject teacher, which is the activity of developing the curriculum in the learning process. Starting from the lesson plans outlined in the RPP, the learning process using creative and varied learning methods, to the assessment process. Evaluation activities are carried out every mid-semester and are also carried out directly when the teacher is experiencing problems during the implementation process.